2005
DOI: 10.1681/asn.2005010001
|View full text |Cite
|
Sign up to set email alerts
|

Additive Antiproteinuric Effect of Pentoxifylline in Patients with Type 2 Diabetes under Angiotensin II Receptor Blockade

Abstract: Despite the beneficial effects of blockade of the renin-angiotensin system in diabetic nephropathy (DN), albuminuria and progression of renal disease are not completely halted by these agents. Therefore, it is necessary to explore potential antiproteinuric and renoprotective effects of innovative therapeutic approaches. This study tested the hypothesis that the combination of pentoxifylline (PTF) with angiotensin II receptor blockers in normotensive patients with type 2 diabetes produces an additive antiprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
90
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 59 publications
7
90
0
1
Order By: Relevance
“…The antiproteinuric effect of this drug is largely ascribed to its inhibitory action on TNF-α and/or TGF-β pathways (20,27,28). In agreement with these reports, the present study shows that PTX can reduce proteinuria in association with attenuation of nephrinuria, downregulation of glomerular NF-κB and Smad signals and restoration of podocyte-related filtration barrier proteins.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The antiproteinuric effect of this drug is largely ascribed to its inhibitory action on TNF-α and/or TGF-β pathways (20,27,28). In agreement with these reports, the present study shows that PTX can reduce proteinuria in association with attenuation of nephrinuria, downregulation of glomerular NF-κB and Smad signals and restoration of podocyte-related filtration barrier proteins.…”
Section: Discussionsupporting
confidence: 91%
“…PTX is a clinically available phosphodiesterase inhibitor that has been shown to reduce proteinuria in various human kidney diseases, including mesangial proliferative glomerulonephritis and IgA nephropathy (19)(20)(21)(22)(23)(24). The antiproteinuric effect of this drug is largely ascribed to its inhibitory action on TNF-α and/or TGF-β pathways (20,27,28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19 We previously reported that PTF administration to diabetic patients resulted in the reduction of clinical markers of glomerular and tubulointerstitial injury. 20,21 In addition, recent meta-analyses indicate that PTF may reduce proteinuria and that this drug could offer some beneficial effects on renal function in patients with DKD. 22,23 Therefore, we conducted the present randomized trial to prospectively test the hypothesis that add-on PTF to maximized ACEI or ARB treatment provides additional benefits against renal disease progression in patients with type 2 diabetes who have stages 3-4 CKD.…”
mentioning
confidence: 99%